An Analisys of Code-Mixing in “Wendy’s Wishes” Novel - Ayu Oktaviani; Kiki Nurmawijayanti; Dewi Syafitri (EDULIA: English Education, Linguistic and Art Journal, 2021)
This study aims to investigate the mixing of the code used in the novel Wendy's Whishes. In this study, researchers used descriptive qualitative methods to investigate utterances in novels. The subjects in this study were writers and characters in the novel. The transcription of the Wendy's Wishes novel contains collected data regarding the reasons people mixed the code. based on research results, in the novel Wendy's Whishes, the author uses several mixing codes. There are thirty-five sayings that have mixed codes in the novel. In conclusion, the author uses thirty-five words that have mixed codes to make conversations in the novel interesting. Keywords: Code Mixing, Novel Wendy's Wishes